2007
DOI: 10.1385/bter:115:1:23
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Zinc, Copper, Leptin, and Body Composition Are Associated in Elite Female Judo Athletes

Abstract: This study evaluated levels of plasma zinc, copper, and leptin, body composition, and their relationship in nine elite female judo athletes under two different training conditions. Body composition and biochemical measurements (hematological indexes, plasma zinc, plasma copper, and plasma leptin) were analyzed 24 h after intense training and following a 5-d period without training (no-training). Plasma leptin and plasma zinc increased with no-training. Plasma zinc correlated negatively with percent fat mass (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
2
13
0
3
Order By: Relevance
“…However, recent studies did not find correlation between serum leptin and fat mass in athletes of different modalities. [8][9][10] These authors suggest that the variation in energy intake is responsible for the lack of relationship between fat mass and the secretion of leptin in athletes. Data from these last studies partly corroborate our data from the PA group, as the individuals have SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies did not find correlation between serum leptin and fat mass in athletes of different modalities. [8][9][10] These authors suggest that the variation in energy intake is responsible for the lack of relationship between fat mass and the secretion of leptin in athletes. Data from these last studies partly corroborate our data from the PA group, as the individuals have SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that the variation in leptin concentration during exercise was related to variation in fat mass. 5,7 However, more recent studies revealed that, regardless of body fat mass change, serum leptin levels are different in athletes 8,9 and in mice. 10 Previous investigations have shown the beneficial effects of physical training on insulin sensitivity in both healthy and glucose-intolerant subjects.…”
Section: Introductionmentioning
confidence: 99%
“…But, low fat proportion may not always indicate low leptin level. This result can be seen in some studies (Koury et al, 2007). They showed that unaltered fat proportion values occurred in spite of low leptin levels after the training (Koury et al, 2007).…”
Section: Introductionmentioning
confidence: 71%
“…This result can be seen in some studies (Koury et al, 2007). They showed that unaltered fat proportion values occurred in spite of low leptin levels after the training (Koury et al, 2007). It is thought that exercise makes its effects on leptin through sympathetic adrenergic system (Torjman, 2001).…”
Section: Introductionmentioning
confidence: 84%
“…However, Olusi et al (2003) recorded no significant relationship between zinc and leptin in healthy adult human. Koury et al (2007) reported that plasma leptin and trace elements were associated with exercising. Mantzoros et al (1998) concluded that Zn may influence serum leptin concentrations, possibly by increasing the production of IL-2 and TNF-α.…”
Section: Discussionmentioning
confidence: 99%